Influence of the Side Group Aromaticity on the Organic Molecule Adsorption on Cu(110) - Rauls, E.; Schmidt, Wolf Gero (Journal of Physical Chemistry C)

Ripening Effects in ZnS Nanoparticle Growth - Tiemann, Michael; Marlow, Frank; Hartikainen, Juha; Weiss, Özlem; Lindén, Mika (The Journal of Physical Chemistry C)
The growth of ZnS nanoparticles during precipitation from aqueous solution is studied by in situ stopped-flow UV absorption spectroscopy at temperatures between 283 and 323 K. Particle growth is marked by substantial ripening during the first 60 ms. Kinetic data suggest that a ripening mechanism by coalescence (oriented attachment) is predominant over Ostwald ripening, although the latter seems to coexist to a significant degree at early temporal stages, predominantly at low temperatures.

The Influence of Catalyst's Oxidation Degree on Carbon Nanotube Growth as a Substrate-Independent Parameter - de los Arcos de Pedro, Maria Teresa; Oelhafen, Peter; Thommen, Verena; Mathys, Daniel (The Journal of Physical Chemistry C)